GOALS AND TASKS OF TEACHING ENGLISH TO PRIMARY CLASS STUDENTS (Academia Science Repository, 2023)
This article talks about the selection of modern educational methods that can be used to develop the motivation of primary school students to learn a foreign language outside the classroom.